The Authority of Ex Officio Judges in Protecting Women's and Children's Rights Post-Divorce at the Manado Religious Court - Salma, Salma; Subeitan, Syahrul Mubarak; Bilalu, Naskur; Zakariah, Asril Amirul; Muhammad, Adamu Abubakar (Jurnal Ilmiah Al-Syir'ah, 2025)
This study examines how judges' ex officio authority is applied to secure the rights of ex-wives and children following a divorce at the Manado Religious Court and the challenges judges face in exercising this authority. It focuses on fulfilling iddah alimony, mut'ah, and child support by the ex-husband and applying ex officio authority in divorce cases. Using an empirical legal approach, the research collects data through in-depth interviews, observations, and documentation. Primary data was gathered from interviews with Manado Religious Court judges and relevant parties, while secondary data was sourced from legal literature and regulations. The findings show that, although legal provisions exist to protect the rights of ex-wives and children, their implementation is hindered by social and economic factors, as well as difficulties in enforcing court decisions. Furthermore, ex officio authority is not always consistently applied, with some judges rarely using it or relying solely on trial evidence. Key challenges include claims of financial incapacity by the ex-husband and lengthy, costly execution processes, undermining the effectiveness of fulfilling these rights. The study also reveals the lack of clarity regarding criminal sanctions for ex-husbands neglecting their alimony obligations.